A REVIEW ON PROMISING ANTIBIOTIC THERAPY BY NOVEL DELIVERY SYSTEMS - R, Priyanka; Bhattacharyya, Sayani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The introduction of a new moiety of drugs for antibiotics in the market is getting declined. Antibiotic resistance is a major threat to human health worldwide. Many life-saving antibiotic drugs are rendered ineffective. Resistant bacterial infections are difficult to treat because of the poor response to antibiotics. Hence, utilizing the novel methods/approaches for the development of formulation into its novel delivery can prevent bacterial resistance. This review article explores the various promising approaches for delivery of antibiotics in the form of liposomes, solid lipid nanoparticles, microspheres, dendrimers, inhaled antibiotics, and polymeric particles. These approaches of delivery have been proven to provide innovative and novel delivery of antibiotic by enhancing the therapeutic effectiveness, targeting at the site of action, enhanced activity, and penetrability at intracellular pathogens, thereby reducing side effects, toxicity, and the chances of bacterial resistance.